Creative Knowledge Sharing For Superior Product Development: A Case Study - Ng, Poh Kiat; Jee, Kian Siong (Journal of Knowledge Management Practice, 2011)
In order for Malaysian manufacturing firms to survive the modern dynamic changes in the existing market, a need has arisen to incorporate knowledge sharing practices with high levels of creativity in product development. With that in mind, this study aims to determine the effect of creative knowledge sharing on product development performance in a Malaysian semiconductor firm. A survey-based method was used to facilitate this study, where a total of 226 survey responses were collected back from the product development engineers of the firm. Using multivariate analyses, it was found that there are significant and positive relationships among knowledge sharing initiatives, creativity and product development performance. However, socialization and externalization initiatives were less dominant compared to combination and internalization initiatives since externalization can be time consuming and socialization captures tacit knowledge that can be overly subjective at times. In conclusion, in order to nurture creative knowledge sharing in product development, it would be beneficial for a firm to provide room for some socialization activities to enrich the idea generation among employees. This paper provides theoretical relevance that explains the mechanisms of knowledge sharing initiatives and creativity in a Malaysian semiconductor firm, with emphasis on the product development process.
Keywords: knowledge management; Knowledge sharing; Engineering performance; Quality; Cross-functional teamwork